Functional Magnefic Resonance Imaging - E. I. Kremneva; R. N. Konovalov; M. V. Krotenkova (Анналы клинической и экспериментальной неврологии, 2017)
Since the early 1990s, fMRI has come to dominate the brainmapping field due to its relatively low invasiveness, absence ofradiation exposure, and relatively wide availability. It measuresthe hemodynamic response related to neural activity in the brain(BOLD-effect). During planning fMRI experiment it is importantto take into account equipment (MRI scan, devices for thestimuli presentation), experimental design and post processing.The last one includes several important steps, such as realignment,co-registration, normalization, smoothing. NowadaysfMRI is widely used not only in research field, especially forcognitive studies, but in clinical practice. However investigatorshould always remember some limitations and controversies,especially in patients with various nosological forms. It is alsoimportant to draw many specialists in experiment and its interpretation neuroradiologists, MR-physicists, clinicians, psychologists,etc. while fMRI is multidisciplinary methodic.